Inner retinal damage after exposure to green diode laser during a laser show - Jeon S (Dove Medical Press, 2014)
Sohee Jeon, Won Ki Lee Department of Ophthalmology, Seoul St Mary’s Hospital, College of Medicine, The Catholic University of Korea, Seoul, Korea Abstract: Here we report two cases of retinal damage after exposure to a 510 nm laser diode during a laser show. The first patient was a 20-year-old female who presented with decreased visual acuity in her right eye after visiting a dance party with a diode laser show (wavelength 510 nm, power 2 mW), although she did not directly see the light. Retinal examination revealed a sub-internal limiting membrane hemorrhage and a small laser burn. The second patient was a 20-year-old female who visited for decreased vision in her left eye. She described similar events as the first patient. An exposure to green diode laser can result in retinal damage. It is strongly recommended that certified personnel operate laser devices used in indoor laser shows under strict regulation. Keywords: green diode laser, sub-internal limiting membrane hemorrhage, inner retinal damage